PERLINDUNGAN HUKUM TERHADAP KREDITUR SEPARATIS PEMEGANG CESSIE DALAM PERKARA KEPAILITAN NOMOR 451/PDT.SUS-PKPU/2021/PN.NIAGA.JKT.PST - Iman Hoeruman; Sudarto (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2025)
This study aims to analyze the legal protection of secured creditors holding Cessie rights in bankruptcy proceedings, based on case No. 451/Pdt.Sus-PKPU/2021/PN.Niaga.Jkt.Pst. Cessie, as a legally valid assignment of receivables under Article 613 of the Indonesian Civil Code, should ensure legal certainty for third-party assignees (cessionaries), including in debtor bankruptcy situations. However, practical implementation reveals several procedural obstacles and normative gaps, causing Cessie holders to often be excluded from recognition as secured creditors, thereby losing their right to priority over the collateral. This research applies normative legal methods, using statutory, doctrinal, and case law approaches. The findings indicate that Indonesia’s current legal framework has not fully accommodated the position of Cessie holders, particularly regarding formal recognition and the inheritance of collateral rights. Therefore, reform of the Bankruptcy Law is necessary to explicitly regulate the legal status of Cessie holders and ensure protection of their rights during debt suspension and bankruptcy asset distribution. This study contributes to strengthening legal certainty and fairness in the national bankruptcy system.